Proceedings of 11th International Conference on Large Scale Applications and Radiation Hardness of Semiconductor Detectors — Po 2015
DOI: 10.22323/1.189.0010
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed laser fabrication of 3D diamond sensors

Abstract: 3D detectors, whose electrodes extend perpendicularly to the sensor surface, represent one of the solution proposed for the challenges of radiation-harsh environments in high energy physics [1][2][3][4]. We report on the fabrication and characterization of prototypes of 3D diamond detector, which add to the 3D architecture the advantages of diamond as a sensor for tracking purposes. Two different laser sources, a Nd:YAG 1064 Q-switched laser with 8 ns pulse-width and a Ti:sapphire laser source with 30 fs pulse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
4
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 15 publications
1
4
0
Order By: Relevance
“…The presence of boundaries and trapping impurities, decreases the charge collection efficiency compared to a single crystal diamond. In different works it has been demonstrated that the charge collection efficiency of a polycrystalline diamond detector ranges from 0.1 to 0.6 the charge collection efficiency of a single crystal diamond detector [14,15]. Furthermore, the sensitivity depends also on the applied bias voltage as well as on the detector leakage current, therefore the obtained sensitivity value is compatible with the expectations for a pCVD diamond device.…”
Section: Sensitivitysupporting
confidence: 65%
“…The presence of boundaries and trapping impurities, decreases the charge collection efficiency compared to a single crystal diamond. In different works it has been demonstrated that the charge collection efficiency of a polycrystalline diamond detector ranges from 0.1 to 0.6 the charge collection efficiency of a single crystal diamond detector [14,15]. Furthermore, the sensitivity depends also on the applied bias voltage as well as on the detector leakage current, therefore the obtained sensitivity value is compatible with the expectations for a pCVD diamond device.…”
Section: Sensitivitysupporting
confidence: 65%
“…The concept of three-dimensional detectors has been conceived for silicon detectors [22] in order to improve the radiation resistance of solid state detectors. In the last years the concept has been also applied to diamond [21,23,24], exploiting the pulsed laser writing techniques made available in the meantime, mainly for optical applications [8].…”
Section: Three-dimensional Diamond Detectorsmentioning
confidence: 99%
“…Its consistent application in radiation sensing occurred after synthetic chemical vapor deposition (CVD) growth of diamond was demonstrated to produce consistent and suitable properties [5,6]. Since then, diamond detectors have been explored for use in extreme environments [7][8][9][10][11], microdosimetry [12,13], and thermal [10,14,15] and fast neutron sensing [10,[16][17][18][19][20], including deuteriumdeuterium (DD) and deuterium-tritium (DT) fusion plasma diagnostics [21,22]. One extreme environment under consideration for diamond detectors is high-rate particle tracking sensors at the LHC [7,[23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%